Modeling the Contribution of Milk to Global Nutrition - Smith, Nick W.; Fletcher, Andrew J.; Hill, Jeremy P.; McNabb, Warren C. (Frontiers in Nutrition, 2022)
Nutrient-rich foods play a major role in countering the challenges of nourishing an increasing global population. Milk is a source of high-quality protein and bioavailable amino acids, several vitamins, and minerals such as calcium. We used the DELTA Model, which calculates the delivery of nutrition from global food production scenarios, to examine the role of milk in global nutrition. Of the 29 nutrients considered by the model, milk contributes to the global availability of 28. Milk is the main contributing food item for calcium (49% of global nutrient availability), Vitamin B2 (24%), lysine (18%), and dietary fat (15%), and contributes more than 10% of global nutrient availability for a further five indispensable amino acids, protein, vitamins A, B5 and B12, phosphorous and potassium. Despite these high contributions to individual nutrients, milk is responsible for only 7% of food energy availability, indicating a valuable contribution to global nutrition without necessitating high concomitant energy intakes. Among the 98 food items considered by the model, milk ranks in the top five contributors to 23 of the 29 nutrients modelled. This quantification of the importance of milk to global nutrition in the current global food system demonstrates the need for the high valuation of this food when considering future changes to the system.